A ReaxFF molecular dynamics study on the hydropyrolysis process of Huadian oil shale kerogen. Issue 4 (4th March 2021) - Zhang, Zhijun; Guo, Liting; Zhang, Hanyu
ABSTRACT : The product distribution and reaction mechanism in the process of Huadian oil shale kerogen hydropyrolysis were investigated via reactive molecular dynamics (RMD) simulations with a reactive force field (ReaxFF). A large-scale reactive system based on 10 Huadian oil shale kerogen structural models was used to investigate the effect of heating rates on the product distribution. Reactive force field molecular dynamics was used to simulate the hydropyrolysis process of the 10 models at four different heating rates of 20, 40, 60 and 80 K/ps. The simulation results proved the influence of heating rate on the product distributions, intermolecular interactions and elementary reactions in the process of hydropyrolysis. A conclusion was made about the suitable heating rate for producing useful organic gases and the highest yield of shale oil. This work also analysed the distribution of hydropyrolytic gas product and the reaction mechanism of Huadian oil shale hydropyrolysis, which is an intensive study on the mechanism of hydropyrolysis and the different formation paths of the symmetrical isoformers of typical products at the atomic level. These conclusions will be of great significance for the development and utilisation of oil shale mineral resources.